Artificial Intelligence as a Learning Companion in the Classroom: Fostering Growth Mindset and Critical Thinking in AI-Assisted Learning Environments - Juwita Sukmaningsih; Muhammad Ainur Rofiq; Wahyu Surya Al Fikri; Mahmuda Ma'arif; Wahyu Nanda Eka Saputra (Buletin Edukasi Indonesia, 2026)
The rapid advancement of artificial intelligence (AI) has significantly transformed educational practices, particularly in classroom learning environments. AI-powered technologies such as intelligent tutoring systems and generative AI platforms provide new opportunities for personalized learning, knowledge exploration, and academic support. However, the integration of AI in education also raises critical concerns regarding the reliability of AI-generated information and the risk of students becoming overly dependent on automated tools. This study explores the role of artificial intelligence as a learning companion in classroom contexts and examines how educators can cultivate growth mindset and critical thinking skills among students in AI-assisted learning environments. Using a qualitative literature-based approach, this study synthesizes recent research on AI in education, AI literacy, and growth mindset pedagogy published between 2022 and 2026. The study proposes a conceptual framework that integrates AI-assisted exploration, critical evaluation of AI-generated knowledge, and reflective learning practices aimed at developing growth mindset among students. The findings indicate that AI should not be viewed as a definitive source of knowledge but rather as a cognitive partner that supports idea generation, information exploration, and collaborative learning. At the same time, students must be trained to critically evaluate AI outputs because AI systems may produce inaccurate or biased information. By integrating growth mindset principles and AI literacy into classroom pedagogy, teachers can help students use AI responsibly while maintaining active intellectual engagement. This study contributes to ongoing discussions about the ethical and pedagogical implications of AI in education and proposes strategies for balancing technological innovation with human cognitive development.